Investigation of the Effect of Calcination Time on the Antibacterial, Antifungal and Anticancer Activities of TiO2/ZnO Nanocomposites - Adil Kadum Shakir; Ebrahim Ghanbari-Adivi; Aref S. Baron Baron; Morteza Soltani (Iranian Journal of Materials Science and Engineering)
Nanomaterials have significantly transformed multiple scientific and technological fields due to their exceptional properties, which result from their quantum confinement effects and high surface-to-volume ratios. Among these materials, zinc oxide (ZnO) and titanium dioxide (TiO2) nanoparticles have attracted considerable interest because of their diverse applications. In this study, TiO2-ZnO nanocomposites were synthesized using varying calcination times of 1, 1.5, 2, 2.5, and 3 hours. Characterization of fabricated samples through X-ray diffraction (XRD)‌ spectroscopy, Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), and energy-dispersive X-ray spectroscopy (EDXS) confirmed the successful fabrication of the nanocomposites. In this regard, XRD analysis revealed anatase TiO2 and hexagonal wurtzite ZnO phases. Raman spectroscopy also supported these findings, identifying characteristic peaks of both TiO2 and ZnO. The calcination time had a minimal effect on the crystal structures and also morphology of the nanocomposites, which gave rise to its negligible impact on optical properties and biological activities of the samples. Optical properties assessed by means of UV-visible and photoluminescence (PL) spectroscopy showed consistent band gap absorption and emission profiles across all samples, among which the nanocomposite calcined for 1 hour exhibited the best optical properties.